Herstory : exploration of the lived experiences of women who were first to lead an HBCU 1994 to 2014 - Lewis, Nichole R (East Carolina University, 2017)
There is increasing scrutiny and accountability being placed on colleges and university in American higher education. Historically black colleges and universities are not exempt from that scrutiny, and in some regards may face it with a higher degree of risk. The criticism and questions of necessity, validity and stability of HBCUs does not come without serious consideration of those who are selected to lead these institutions. This study explores the lived experiences of black women who were selected as the first women to lead three HBCUs between 1994 and 2014. This time-bound period was selected as there was a significant increase in the selection of women to serve as presidents of colleges and university, with HBCUs and community colleges experiencing the highest increases, as the governing boards of those institutions were selecting black women to take the helm. This qualitative study uses narrative inquiry to specifically explore the transition period into the presidency, the first 100 days in the role and the final 100 days in the position as permanent HBCU president or chancellor. Considering the conceptual theory of the Glass Cliff, findings are used to draw meaning from the experiences of these women, that may serve as guidance for African-American women who are considering a career path that ends in the presidential suite. The narratives explored in this study are the stories of Dr. T.J. Bryan - Fayetteville State University, Dr. Dianne Boardley Suber - Saint Augustine's University, and Dr. Dorothy Cowser Yancy - Johnson C. Smith University, all located in the state of North Carolina.
Keywords: HBCU; African American women college administrators--North Carolina; African American universities and colleges--North Carolina; Glass cliff (Employment discrimination); Educational leadership; Fayetteville State University; Saint Augustine's University; Johnson C. Smith University